DEVELOPMENT OF CITIZENSHIP LEARNING BASED ON MORAL INTELLIGENCE AS A SYSTEM PROGRAM FOR CULTURING MAIN CHARACTER VALUES - Deny Setiawan; Arief Wahyudi (Teunuleh Publisher, 2020)
This research was motivated by the factual condition of the occurrence of a moral crisis among Indonesia's young generation, including the weak culture of the main character values. This development research was aimed to develop moral intelligence-based Citizenship Education learning as a systemic program for the culture of the main character values. The scope of this research was limited to the study of civics learning based on moral intelligence as a systemic program of cultivating character values among students. The research method was used by the Research & Development. The research subjects involved: (1) a lecturer who taught introduction courses of civics; (2) students is limited group trials as subject; and (3) three experts for the validation of teaching materials who had criteria for Citizenship Education experts including: politics, law, and moral philosophy. The instrument was used an expert validation questionnaire which was analyzed using the Percentage Mean Score (PRS). The results of the research showed that civics learning textbook based on intelligent moral that developed was very valid and suitable for being used and giving contribution on the strengthen of character for students in their scope life in global era that full of change and value paradoxes.